THE GENETIC SUSCEPTIBILITY TO ATHEROSCLEROSIS - T. V. Kozhanova; E. V. Neudakhin; S. S. Zhilina; T. I. Mescheryakova; A. A. Abramov; E. N. Lukash; A. G. Prityko (Архивъ внутренней медицины)
Atherosclerosis is a complex multifocal arterial disease involving interactions of multiple genetic and environmental factors. Atherosclerosis is the main cause of death and disability in developed countries, while in developing countries the incidence of this pathology is growing rapidly. Advances in techniques of molecular genetics have revealed that genetic polymorphisms significantly influence susceptibility to atherosclerotic vascular diseases. A large number of candidate genes, genetic polymorphisms and susceptibility loci associated with atherosclerotic diseases have been identified in recent years and their number is rapidly increasing. In recent years, there is significant interest in identifying additional factors of genetic risk for atherosclerosis. In recent years, a large number of genetic studies have been carried out to prove the genetic effect on the atherosclerotic process. Rapid progress in the sequencing of the human genome and molecular genetic methods have helped in the definition of susceptibility loci and associated candidate genes with atherosclerosis and concomitant diseases. The association of a large number of susceptibility genes with atherosclerosis reflects the enormous complexity of the disease. Multiple factors, including endothelial dysfunction, lipid metabolism defects, inflammation and immune responses, oxidative stress, cell proliferation, tissue remodeling and hemostatic defects are involved in the pathogenesis of atherosclerosis. In this review we focus and discuss on some of the major candidate genes and genetic polymorphisms associated with human atherosclerotic vascular diseases.